Reimagining Government with the Ethics of Care: A Department of Care. Issue 3 (2nd July 2020) - FitzGerald, Maggie
ABSTRACT: The question of how to apply care ethics to institutions and social policies has been much discussed, with recent research expanding the scope of care ethics policy analysis to policy areas that are generally not viewed as 'care related'. This paper seeks to engage with this literature in a critical and constructive way to explore more fully the transformative potential of the ethics of care. In particular, this paper argues that the aforementioned literature uses care ethics to focus on practices of care, as opposed to employing the ethics of care as a critical political theory (Robinson, Fiona. 2018. "Resisting Hierarchies through Relationality in the Ethics of Care." International Journal of Care and Caring XX (xx): 1–13). While such analyses are important, this paper proposes a 'Department of Care' as a thought experiment to demonstrate how the ethics of care, as a critical political theory, allows for a radical critique of institutions and governing norms, and inherently destabilizes the dominant understandings of the purpose, structure, and role of government and public policy.